Pembentukan Karakter Peduli Lingkungan Melalui Pembelajaran Tematik Pada Pendidikan Anak Usia Dini - Margarith Loho; Orient Christianty (Peneliti.net, 2023)
This research is a research that uses qualitative methods and aims to find out and describe how the character formation of caring for the environment through thematic learning. Data collection techniques are carried out through observation, interviews and documentation studies. The results show that: (1) Implementation of thematic learning with a scientific approach that refers to curriculum 13 has been carried out at GMIM Bethesda Bitung Kindergarten, (2) Learning stages which include opening activities, core activities and closing activities already contain the values ​​of environmental care character especially on the theme of my environment, plants and animals, 3). The formation of the character of caring for the environment in students is formed through habituation that is carried out both in the opening activities, core activities, and closing learning activities. From the results of the study, it is suggested that parents of students can continue the habituation that is taught and trained by teachers at school so that the formation of the character of caring for the environment in students can be maximized and not interrupted only until the learning process is carried out at school.